Public Sector-operated Price-comparison Websites : Case Studies and Good Practices - World Bank (Washington, DC, 2013)
This technical note is intended to provide regulators with concrete, practical information on operating price-comparison websites and the strategic considerations necessary to take into account when designing such sites. The technical note examines price-comparison websites operated by public sector entities in Canada, Hungary, Ireland, Malaysia, Mexico, Norway, and the United Kingdom. The technical note describes the price-comparison tools in these case study countries, comparing differing approaches and highlighting good practices found across countries. Institutional and structural arrangements were found to vary across case study countries. Price-comparison websites are operated by either a financial regulator (Hungary, Malaysia) or more commonly by a financial consumer agency set up by the government but operating as an independent agency (Canada, Ireland, Mexico, Norway, United Kingdom). Typically, less sophisticated price-comparison websites provide basic price-comparison tools, while more sophisticated sites provide interactive product-selection tools and complementary educational materials in an intuitive, easy-to-use format.